Combination therapy for the treatment of autoimmune diseases - PARNHAM MICHAEL; CHRISTEN URS; LASCH STANLEY (2017)
The present invention pertains to compounds and their combination for use in the prevention or therapy of a subject suffering from an autoimmune disease such as diabetes type 1. Provided are antagonists of T-cells that are used in combination with antagonists of the cytokine CXCL10, sequentially or concomitantly, in a subject suffering from an autoimmune disease, in particular diabetes type 1. 本发明涉及用于预防或治疗患有自身免疫性疾病如1型糖尿病的受试者的化合物及它们的联合。本发明提供了T细胞拮抗剂，所述T细胞拮抗剂在患有自身免疫性疾病特别是1型糖尿病的受试者中顺次地或同时地与细胞因子CXCL10拮抗剂联合使用。